Strengthening the enforcement of policy to combat human trafficking: a network approach for improving collaboration - Patel, Jaynisha (Department of Philosophy, 2020)
Modern-day slavery, now termed human trafficking, is a crime that has remerged in the modern day. It is a transnational crime through which a humans vulnerability is exploited through coercive means. In recent decades the issue has attracted policy and legislative attention from governments, however these responses have failed to effectively respond to the complex dimensions of the phenomena. Alongside state measures to reduce the crime have been networks of understudied non-governmental organisations dedicated to combatting human trafficking. As non-governmental organisations develop capacity and knowledge to combat human trafficking they have often become key stakeholders in the field. In this dissertation, I examine to what extent the efforts of NGOs are aligned with the South African Government policy and legislative agenda in dealing with human trafficking. My aim is to determine the extent of alignment and, through applying a policy network framework, what the prospects are for improved collaboration between NGOs and the state. To determine how a collaborative network response can strengthen South Africa's enforcement of anti-trafficking policy, I have used secondary and collected new primary data. Primary data consists of data gathered through a survey of NGOs working on human trafficking in South Africa from which the scope of the reach, activities, and experiences of these stakeholders can inform prospects for collaboration – to improve enforcement of anti-trafficking measures. Findings suggest that a network approach to improve collaboration between the state and non-state stakeholders will be most effective across activities where the state has performed poorly, and where NGOs have displayed a comparative advantage. These activities include prevention-related work such as public awareness, equipping first responders with knowledge through training on human trafficking and legislation, and victim assistance together with aftercare.